Reflections About The Controversy Of Indigenism - Macera, Pablo (1977)
This article had its origin in the comments on the book The Controversy Of Indigenism, José Carlos Mariátegui - Luis Alberto Sánchez (Lima, Mosca Azul Editores, 1975); the references of the author comes from that.